The Effect of Marketing Strategies, Consumer Behavior, and Brand Equity on Business Expansion in the Retail Sector - Tubalawony, Jacsy (IJBLE Scientific Publications Community Inc., 2024)
This study explores the effects of marketing strategies, consumer behavior, and brand equity on business expansion within the retail sector. Using a quantitative approach, data were collected from 250 retail businesses and analyzed through multiple regression analysis. The results indicate that marketing strategies, consumer behavior, and brand equity each significantly influence business expansion, with brand equity showing the strongest effect. These findings underscore the importance of a comprehensive approach that combines strategic marketing, an understanding of consumer behavior, and strong brand management for achieving sustainable business growth. The study provides practical insights for retail managers and contributes to the existing literature by highlighting the combined impact of these factors on business performance.